SIMULATION OF BEHAVIOR OF A BATCH DISTILLATION COLUMN FOR MIXTURES USING SHORT METHODS MULTICOMPONENT - Romero, P. (2009)
Short method is presented to simulate the behavior of a batch distillation column with rectifying ideal multicomponent mixture refluxed constante.El method is to consider the behavior of discontinuous column as operating a continuous distillation column in short periods time and use the method of Fenske-Underwood-Gilliland (FUG) to estimate the compositions of the distillate.